1989
DOI: 10.1128/aac.33.2.164
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to cephalosporins of penicillin-susceptible and penicillin-resistant strains of Neisseria gonorrhoeae from Philadelphia

Abstract: Using agar dilution, we determined MICs of penicillin, cefoxitin, ceftriaxone, cefmetazole, tetracycline, and spectinomycin for 129 strains of Neisseria gonorrhoeae. All strains were susceptible to ceftriaxone (MIC range, .0.008 to 0.06 ,ug/ml) and spectinomycin (16 to 32 ,ug/ml). The MICs for 50, 90, and 100% of strains tested were 1.0, 2.0, and >8.0 ,ug/ml; 0.12, 1.0, and >8.0 ,Ig/ml; 0.5, 1.0, and 2.0 ,ug/ml; and 1.0, 2.0, and >8.0 ,ug/ml for cefmetazole, penicillin, cefoxitin, and tetracycline, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1990
1990
1995
1995

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…In the large cooperative study designed to set up quality control criteria for disk diffusion and agar dilution AST, the r values were 0.97 for penicillin, 0.88 for tetracycline, and 0.65 for ceftriaxone (57). In our study in 1991, the r values were 0.96 for penicillin, 0.94 for tetracycline, 0.62 for ceftriaxone, and 0.62 for cefpodoxime (34). Similar findings were reported for two other very potent cephalosporins: cefotaxime had an r value of 0.79, and ceftazidime had a value of 0.63 (55).…”
Section: Cephalosporinssupporting
confidence: 75%
“…In the large cooperative study designed to set up quality control criteria for disk diffusion and agar dilution AST, the r values were 0.97 for penicillin, 0.88 for tetracycline, and 0.65 for ceftriaxone (57). In our study in 1991, the r values were 0.96 for penicillin, 0.94 for tetracycline, 0.62 for ceftriaxone, and 0.62 for cefpodoxime (34). Similar findings were reported for two other very potent cephalosporins: cefotaxime had an r value of 0.79, and ceftazidime had a value of 0.63 (55).…”
Section: Cephalosporinssupporting
confidence: 75%
“…Furthermore, if there is emergence of strains with diminished susceptibilities to ceftriaxone, cefpodoxime may also be of limited value. In an earlier study, we found a similar association between MICs for cefoxitin and cefmetazole in ,-lactamase-negative strains (6). The ultimate determination of MIC breakpoints and disk diffusion zone diameter cutoffs for cefpodoxime will best be made when clinical data reg4rding the correlation of cure rates with MICs are available.…”
Section: Discussionmentioning
confidence: 91%
“…In many geographic areas, penicillin and tetracycline are very likely to result in failure of therapy because of the high prevalence of resistant strains. Penicillin and tetracycline MICs can be well estimated by using disk diffusion as in previous studies (6,8). The accuracy of disk diffusion testing for ceftriaxone and cefpodoxime is somewhat less, but it is still reproducible.…”
Section: Discussionmentioning
confidence: 99%
“…One of the concerns about the 1-lactamase-stable cephalosporins is that, for non-PPNG strains, the MIC of penicillin is highly correlated with the MIC of the cephalosporin. In Philadelphia in 1989, we showed a strong log-linear correlation between penicillin and cefmetazole MICs for 122 non-PPNG strains (Pearson r = 0.787) (34). Several strains had cefmetazole MICs of .4 ,ug/ml, suggesting that they might not be eradicated with single-dose cefmetazole.…”
Section: Cephalosporinsmentioning
confidence: 87%